A new species of dusky salamander (Amphibia: Plethodontidae: Desmognathus) from the Eastern Gulf Coastal Plain of the United States and a redescription of D. auriculatus - Means, D. Bruce; Lamb, Jennifer Y.; Bernardo, Joseph (Zootaxa, 2017)
The Coastal Plain of the southeastern U. S. is one of the planet’s top biodiversity hotspots and yet many taxa have not been adequately studied. The plethodontid salamander, Desmognathus auriculatus, was originally thought to occur from east Texas to Virginia, a range spanning dozens of interfluves and large river systems. Beamer and Lamb (2008) found five independent mitochondrial lineages of what has been called D. auriculatus in the Atlantic Coastal Plain, but did not examine the extensive distribution of D. auriculatus in the Gulf Coastal Plain. We present morphological and molecular genetic data distinguishing two evolutionarily independent and distantly related lineages that are currently subsumed under the taxon D. auriculatus in the eastern Gulf Coastal Plain. We describe one of these as a new species, Desmognathus valentinei sp. nov., and assign the second one to D. auriculatus which we formally redescribe.